Effect of Human Immunodeficiency Virus (HIV) Infection on Mortality Among Hospitalised COVID-19 Patients at Levy Mwanawasa University Teaching Hospital, Lusaka, Zambia - John Nsakulula; Given Moonga; Jeremiah Banda; Patrick Musonda (COVID)
Emerging but limited evidence suggests that HIV infection does not affect in-hospital COVID-19 mortality, regardless of the prevalence of HIV infection in most parts of sub-Saharan Africa, especially the southern Africa region, and Zambia, Lusaka District in particular, is not an exception. Therefore, this study aimed to determine the effect of HIV infection, demographics, and clinical factors on mortality among hospitalized COVID-19 patients at Levy Mwanawasa University Teaching Hospital (LMUTH). A cross-sectional study was conducted with a sample size of 698 adults admitted for COVID-19 at LMUTH from 18 March 2020 to 31 December 2021. For all statistical analysis of data, STATA statistical software, version 15 MP (College Station, TX 77845, USA) was used—ensuring that appropriate statistical techniques were applied to the data. Unadjusted and adjusted logistic regressions were conducted to model COVID-19 mortality among COVID-19 patients based on their HIV status while controlling for five predictor variables. Based on the results, the best predictors of in-hospital COVID-19 mortality were HIV status, number of comorbidities, age in years, smoking, and alcohol intake. The results suggest that COVID-19 mortality among those with HIV and those without HIV infection was different. People living with HIV infection had increased odds of COVID-19 mortality compared to those without HIV. The results further suggested that a unit increase in age was associated with increased odds of COVID-19 mortality. Furthermore, drinking alcohol and having two or more comorbidities increased the odds of COVID-19 mortality compared to not drinking alcohol, having no comorbidity, or having a comorbidity. This study, therefore, concludes that HIV infection has a significant effect on COVID-19 mortality among patients hospitalized at LMUTH and that the proportion of COVID-19 mortality in the HIV-infected group is relatively higher than in the uninfected group. Therefore, there is a need for close monitoring of COVID-19 patients with HIV infection.